Does Heel Height Cause Imbalance during Sit-to-Stand Task: Surface EMG Perspective - Naik, Ganesh R.; Al-Ani, Ahmed; Gobbo, Massimiliano; Nguyen, Hung T. (Frontiers in Physiology, 2017)
The purpose of this study was to determine whether electromyography muscle activities around the knee differ during sit-to-stand and returning task for females wearing shoes with different heel heights. Sixteen healthy young women (age = 25.2 ± 3.9 years, body mass index = 20.8 ± 2.7 kg/m2) participated in this study. Electromyography signals were recorded from the two muscles, vastus medialis and vastus lateralis that involve in the extension of knee. The participants wore shoes with five different heights, including 4cm, 6cm, 8cm, 10cm and 12cm. Surface electromyography data were acquired during sit-to-stand, and stand-to-sit-returning tasks. The data was filtered using a 4th order Butterworth (band pass) filter of 20Hz – 450Hz frequency range. For each heel height, we extracted median frequency and root mean square features to measure sEMG activities between vastus medialis and vastus lateralis muscles. The experimental results (based on median frequency and root mean square values) indicated that there is imbalance between vasti muscles for more elevated heels. The results are also quantified with statistical measures. The study findings suggest that there would be an increased likelihood of knee imbalance and fatigue with regular usage of high heel shoes in women.